George Town, Penang, as a UNESCO World Heritage Site: a showcase of best practises in heritage conservation and sustainable development - Muhamad Ferdhaus,; Hasnizam Ab Dulhamid,; Mohamad Azal Fikri Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
George Town in Penang is recognised as a UNESCO World Heritage Site in Malaysia. This article explores the case study of George Town, a UNESCO World Heritage Site in Penang, Malaysia, focusing on its exemplary qualities. Including George Town in the UNESCO World Historical List 2008 was a notable achievement in historic preservation and urban growth. The primary aim of this essay is to analyse the effective strategies used in the preservation of George Town's cultural, architectural, and historical authenticity while concurrently fostering sustainable growth by two main primary entities: the City Council of Penang Island (MBPP) and George Town World Heritage Incorporated (GTWHI). Implementing these conservation programmes has not only resulted in preserving the city's physical and intangible history but has also revitalised its historic districts, thereby converting them into thriving centres for artistic expression, cultural activities, and tourist attractions. This article thoroughly examines relevant literature, policy papers, and on-site observations to elucidate the significant methods, problems, and results that have characterised George Town's progression as a World Heritage Site. The insights derived from the experience of George Town provide useful lessons for other cultural sites seeking to achieve a peaceful equilibrium between preservation, conservation, and future development.